(untitled) (Journal of Atomic and Molecular Sciences, 2012)
Various scattering cross section such as differential, integrated elastic, momentum transfer, total cross-sections and spin polarization parameters for both the elastic and total scattering of electron and positron from Re atoms in the impact energy range between 2.0 to 500 eV using the relativistic Dirac equations are studied. The target-projectile interaction is included by real and complex-free optical potentials for obtaining the solutions of Dirac equation for scattered electrons and positron. The Dirac-Fock wave functions have been used to represent the e^±-Re target atoms. Corresponding theoretical results are obtained from a relativistic approach based on solving the Dirac equation using Hartree-Fock and Dirac-Fock wave functions to calculate cross sections at all the energies measured.